2005
DOI: 10.1590/s1415-52732005000400006
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos dos óleos de amendoim, açafrão e oliva na composição corporal, metabolismo energético, perfil lipídico e ingestão alimentar de indivíduos eutróficos normolipidêmicos

Abstract: OBJETIVOS: O presente trabalho visou avaliar os efeitos do consumo dos óleos de amendoim, açafrão e oliva no perfil lipídico, composição corporal, metabolismo energético e ingestão alimentar em indivíduos eutróficos normolipidêmicos. MÉTODOS: Foram selecionados 32 indivíduos, divididos aleatoriamente em quatro grupos, tendo quatro mulheres e quatro homens em cada grupo, com idade entre 18 e 50 anos. Foi oferecido um milk shake aos voluntários no desjejum, veiculando uma quantidade equivalente a 30% da sua ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
2
0
2
Order By: Relevance
“…The characteristics of the included studies are shown in Table 1. Among the 52 studies selected, 44 7,17–21,28–66 are randomized clinical trials with a parallel design and eight 67–74 have a crossover design. The samples of the included studies ranged from 23 to 351 participants, with a mean age ranging from 23 to 79 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the included studies are shown in Table 1. Among the 52 studies selected, 44 7,17–21,28–66 are randomized clinical trials with a parallel design and eight 67–74 have a crossover design. The samples of the included studies ranged from 23 to 351 participants, with a mean age ranging from 23 to 79 years.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding body composition, the outcomes of total body adiposity (in kilograms and percentage) and lean mass were evaluated through meta-analysis. Body composition was assessed by dual-energy X-ray absorptiometry (DXA) in 12 studies, 7,19,33,35,36,39,40,42,50,57,60,66 by bioelectric impedance in 17 studies, 29,31,38,41,47,48,[51][52][53][54][55][56]58,61,65,67,73 by plethysmography system in two studies 17,63 and in another body fat was calculated from the three-compartment model based on measurement of skin fold thick. 21 The other studies utilized computed tomography and DXA 59 or bioelectric impedance.…”
Section: Reviewmentioning
confidence: 99%
“…Chestnut is a gluten free fruit, mostly composed of complex carbs, but it also contains a considerable number of proteins (with high biological value) and fibers, which help to control insulin response and cholesterol levels [26]. Compared to other nuts and dried fruits, it is a fruit with a low-fat content [26,27] and an excellent source of vitamins, namely B6, vitamin C and folic acid [28]. It also has a relevant quantity of minerals such as calcium, copper, iron, manganese, magnesium, potassium, phosphorus, selenium and zinc [29].…”
Section: Fruit Nutritional Characterizationmentioning
confidence: 99%
“…8 Além disso, o consumo de ácidos graxos poliinsaturados e de ácidos graxos monoinsaturados tem sido recomendado para melhorar o perfil lipídico em relação aos ácidos graxos saturados. 9 A composição do café e sua repercussão sobre a saúde humana, notadamente sobre as doenças cardiovasculares, vêm sendo objeto de muitos estudos, cujos resultados são conflitantes. Tal fato, provavelmente, se deve à presença de substâncias com efeitos antagônicos em potencial, ou seja, ao mesmo tempo antioxidantes e com potencial para a elevação do colesterol sérico e para o aumento agudo da pressão arterial sistêmica.…”
Section: Hábitos Alimentar Hábitos Alimentar Hábitos Alimentar Hábitounclassified